Diagnosis and possible phylogenetic relationships of psorophora (Grabhamia) dimidiata (Diptera : Culicidae) - Stein, Marina (2022)
Fil: Stein, Marina. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.